Implementasi Program Nasional Pemberdayaan Masyarakat Mandiri Pedesaan (PNPM) Di Desa Salam Tani Kecamatan Pancur Batu Kabupaten Deli Serdang - Ridhon Simangunsong (Jurnal Ilmu Sosial Dan Politik, 2022)
The purpose of this study was to determine the implementation process and determine the performance of PNPM-MP implementation on the SPP program in Salam Tani Village, Pancur Batu District, Deli Serdang Regency. This study used descriptive qualitative method. Sources of data are Salam Tani Village Head, PNPM TPK Chair, SPP group chairman, Community members who are members of the Women's Savings and Loans Group. Women's Savings and Loans in Salam Tani Village, Pancur Batu District is classified as a fairly good program. The performance of PNPM-MP implementation in the SPP Program has been good, this can be seen from the results of activities which provide positive benefits for the community (women). Has been able to help local communities in improving the economy and a good standard of living. In the future, there is a need for better mobilization of resources, more training and guidance needs to be developed, a system is needed to monitor the use of funds by SPP recipients. This program must receive greater attention from related parties so that the activities carried out are even better, especially at the village level.